Vitamin B6 and glucose control: a forgotten role in prediabetics? Narrative review - Mohammed, Hajer; M. Mustafa , Mariam (Libyan Journal of Medical and Applied Sciences, 2026)
Prediabetes is an international health concern increasing the risk of progression for diabetes and cardiovascular disease. Although hyperglycemia management guidelines emphasize macronutrient intake and lifestyle modification, the role of micronutrients in these guidelines has been neglected. Thus, the underestimated role of B6 in short glucose regulation, particularly in prediabetes, is addressed in this review. One of the largest epidemiological studies, the National Health and Nutrition Survey, demonstrated a significant inverse association between dysglycemia and B6 level. In this study each 1 mg increase in B6 lowered odds of dysglycemia by 15%. On a biochemical level pyridoxal 5 phosphate, the biologically active form of B6, is an essential cofactor in 150 enzymatic reactions, a strong carbonyl scavenger, and an inhibitor of advanced glycation end product formation, which is crucial for complication development. Moreover, B6 has antioxidant and anti-inflammatory qualities, supports B cell function, and influences intestinal glucose by blocking alpha-glucosidase. The clinical use of B6 in the treatment of prediabetes is neglected despite the strong body of data from observational and mechanical studies. Furthermore, there is a substantial disconnect between robust epidemiological studies and clinical practice and a lack of conclusive clinical trials. Thus, this review study aims to indicate B6 as a plausible modifiable determinant of dysglycemia in prediabetes that needs a targeted, rigorous intervention trial with the objectives to determine its efficacy, appropriate dosage, and therapeutic significance in its management and prevention.